De novo assembly and comparative analysis of the mitochondrial genome of Reynoutria japonica - Chen, Jianhui; Ma, Hongping; Fan, Haili; Lin, Fan; Chai, Tuanyao; Wang, Hong (Frontiers in Genetics, 2023)
Reynoutria japonica Houtt. is an important medical plant with a long history of thousands of years in China, however, its mitochondrial genome (mitogenome) has not been reported yet. In this work, we reported and analyzed the R. japonica mitogenome. The main results include: The R. japonica mitogenome was 302,229 bp in length and encoded 48 genes, including 27 protein-coding genes (PCGs), 3 rRNA genes, and 18 tRNA genes. Repeat sequence analysis revealed that there were 54 repeat sequences ranging from 193 bp to 1,983 bp in the R. japonica mitogenome. Relative synonymous codon usage (RSCU) analysis showed that leucine (900, 11.01%) and serine (732, 8.96%) were the two most abundant amino acids, and the codons with RSCU values showed the preference of A or T ending when greater than 1. The RNA editing sites of PCGs in the R. japonica mitogenome were characterized, and 299 RNA editing sites were found. Extensive sequences transfer between mitochondrion and chloroplast were found in R. japonica, where 11 complete plastid-derived tRNA genes stayed intact in the R. japonica mitogenome. Three genes (ccmFC, cox1, and nad1) were seen to play essential roles in the evolution through selection pressure analysis. The phylogenetic analysis showed that Fallopia multiflora was the closest species with R. japonica, in consistency with the results of chloroplast genome. Overall, the current work presents the first mitogenome of R. japonica and could contribute to the phylogenetic analysis of the family Polygonaceae.